Infecção latente por tuberculose: uma análise dos componentes e indicadores epidemiológicos do tratamento preventivo da tuberculose em Goiás - Gomes, Daniel Batista (2016)
Tuberculosis is still a major global health problem. One of the strategies recommended for the control of tuberculosis is the identification and early treatment of individuals with latent M. tuberculosis infection (ILTB). In Brazil, ILTB is not part of the compulsory notification aggravations, but there is a recommendation for States to create instruments for notification and follow-up of cases. In Goiás, a notification form for ILTB was developed in 2012 by the State Department of Health. The objective of the research is to analyze the epidemiological profile of ILTB cases and to characterize the surveillance processes related to the diagnosis and treatment of this disease in this state. The reports of ILTB cases treated between 2013 and 2015 were analyzed. A database linking was carried out considering the cases of tuberculosis reported in the SINAN NET Notification System and the ILTB records. To evaluate the technical and structure aspects of ILTB control services, a structured questionnaire was applied to the supervisors of health surveillance in the 18 health regions of the State. A descriptive and exploratory data analysis was carried out using software SPSS 13.0 and TABWIN 1.6 EPI INFO. 345 cases of ILTB were reported in the study period. The patients' ages ranged from 0 to 92 years (median age 38 years); 65.2% were adults and 10.1% were up to 10 years. Five municipalities (Goiânia, Aparecida de Goiânia, Jataí, Anápolis and Formosa) reported 77.7% of the cases. In 24.6% of the cases, the criterion for treatment of ILTB was the result of Tuberculin Test (TT)> 10mm. In this group all cases were asymptomatic and 78.8% had contact with active tuberculosis. It was identified that 39 cases were HIV positive, corresponding to 12.7% of indications for ILTB treatment. According to health surveillance supervisors, all 246 municipalities had a Tuberculosis Control Program. Concerning the specific training on ILTB, 74 municipalities (30.1%) received this training, reaching 141 health professionals. In relation to the specific training for the application of TT, only three (16.7%) health regions were trained, of which two managed to decentralize this training to some of their jurisdictions. Eleven regional health (61.1%) reported that the number of TT provided by the State Department of Health was inadequate to meet the demands of municipalities. According to supervisors, 88.2% of the municipalities in Goiás do not have the tools to monitor cases of co-infection with HIV. The present study contributed to the knowledge of the epidemiological profile of the reported cases of ILTB, as well as to the process of control of this aggravation in the State. Failures were identified in the ILTB control process in the different regions of the State of Goiás. This study is expected to support effective actions to control tuberculosis in the State.